Manajemen Kepemimpinan Transformatif dalam Mengembangkan Budaya Literasi di Sekolah Dasar Negeri 34 Sebelitak - Wulandari; Maria Adventina Sunardiyah; Susilo Surahman; Pandu Adi Cakranegara; Hermyn B. Hina (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2022)
The existence of a very fast world shift in the world of education in a globalized manner provides a new direction in developing deep thinking with the existence of very sophisticated technology. The literacy we face today is indeed very quickly accepted and requires a lot of understanding and data. The research objective was to describe and analyze the implementation of transformational leadership by school principals to create a culture of literacy for teachers and students in schools. The research method with qualitative research with a phenomenological approach. Primary data sources in research; principals, teachers and students. Data collection tool with interviews, observation and documentation. Data analysis uses data reduction, data presentation, and conclusion or verification. Research result; transformative school principal programs include holding workshops on the use of digital literacy every 1 semester 2 times, in sub-district KKG events and utilizing social media in communicating and utilizing internet media as a learning medium.